2015
DOI: 10.1021/jacs.5b08143
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Tip-Enhanced Raman Spectroscopy

Abstract: Interfacial properties are highly important to the performance of some energy-related systems. The in-depth understanding of the interface requires highly sensitive in situ techniques that can provide fingerprint molecular information at nanometer resolution. We developed an electrochemical tip-enhanced Raman spectroscopy (EC-TERS) by introduction of the light horizontally to the EC-STM cell to minimize the optical distortion and to keep the TERS measurement under a well-controlled condition. We obtained poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
240
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(246 citation statements)
references
References 26 publications
5
240
0
1
Order By: Relevance
“…Further applications of liquid TERS have since been demonstrated, including the analysis of lipid bilayers [131], the adsorption of probe molecules on Au(111) [132], and TERS imaging in organic liquids [133]. It has taken several years since the first demonstration of liquid TERS to develop EC-TERS but 2015 saw major advances from two independent groups [134,135]. Ren et al employed an STM-TERS approach with horizontal illumination (see Figure 6(a)-(d)) to obtain EC-TERS spectra of molecular monolayers adsorbed at single crystal Au electrodes, and reported significant changes brought about by the potential-induced protonation/deprotonation of the surface-adsorbed species [135].…”
Section: Ec-tersmentioning
confidence: 99%
See 1 more Smart Citation
“…Further applications of liquid TERS have since been demonstrated, including the analysis of lipid bilayers [131], the adsorption of probe molecules on Au(111) [132], and TERS imaging in organic liquids [133]. It has taken several years since the first demonstration of liquid TERS to develop EC-TERS but 2015 saw major advances from two independent groups [134,135]. Ren et al employed an STM-TERS approach with horizontal illumination (see Figure 6(a)-(d)) to obtain EC-TERS spectra of molecular monolayers adsorbed at single crystal Au electrodes, and reported significant changes brought about by the potential-induced protonation/deprotonation of the surface-adsorbed species [135].…”
Section: Ec-tersmentioning
confidence: 99%
“…It has taken several years since the first demonstration of liquid TERS to develop EC-TERS but 2015 saw major advances from two independent groups [134,135]. Ren et al employed an STM-TERS approach with horizontal illumination (see Figure 6(a)-(d)) to obtain EC-TERS spectra of molecular monolayers adsorbed at single crystal Au electrodes, and reported significant changes brought about by the potential-induced protonation/deprotonation of the surface-adsorbed species [135]. Using an AFM-TERS configuration, Van Duyne and co-workers studied the redox behaviour of NB at indium tin oxide (ITO) electrodes and postulated that, because of the scale of the experiment, the TERS probe perturbs the electrical double-layer and hence affects the local potential experienced by the molecules at the surface [134].…”
Section: Ec-tersmentioning
confidence: 99%
“…8 They were able to acquire spectra from less than 600 molecules within a nanoreactor defined by the distance between the probe tip and substrate surface (<10 nm). Braunschweig and co-workers utilized the solution volume between elastomeric tips and a surface as nanoreactors to investigate the effect of applied force and chain length on the reaction rate of the copper-free Huisgen cycloaddition between an alkyne and a surface-bound azide.…”
mentioning
confidence: 99%
“…Recently, the Ren group reported that STM EC-TERS could be utilized to monitor arrangements of 4 ′ -(pyridin-4-yl)biphenyl-4-yl) methanethiol (4-PBT) on Au(111) as a result of its protonation and deprotonation [77]. The authors pointed out that such information about potential-dependent re-configuration of 4-PBT could not be obtained from EC-SERS experiments.…”
Section: Electrochemical Scanning Probe Microscopy and Tersmentioning
confidence: 99%
“…This work demonstrated that insulation of STM tips, necessary for reducing Faradaic current from tip shaft, could be successfully achieved. Zeng et al proposed to embed freshly etched Au or Ag wire into polyethylene glue, which allowed the tip apex to remain plasmonically active [77].…”
Section: Electrochemical Scanning Probe Microscopy and Tersmentioning
confidence: 99%